A new species of Velarifictorus Randell, 1964 (Orthoptera: Gryllidae: Gryllnae: Modicoryllini) bearing similarities to the Landrevinae from China - Ma, Libin; Qiao, Min; Zhang, Tao (Zootaxa, 2019)
Three species of Velarifictorus bear similarities to those of the Landrevinae. They are V. elephas Gorochov, 1992, V. bubalus Gorochov, 1992 and V. gradifrons Ingrisch, 1998. They are stout, reddish or chocolate brown colored. Here, another similar new species is described from China.